Reseach on Demand for Training Bachelor of Clinical Psychology for Health Facilities - Kien, Pham Trung; Huong, Tran Thu (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
Research on the psychological difficulties and need of mental care for patients and their relatives in the hospital are basic to determine demand for training and using staffs for psychological care. The obtained results found that 32.5% of patients in the hospital had psychological difficulties; percentage of patients who need to share with the medical staff was 42.0%; there had 41.0% of patients in need of comprehensive care; 51.5% of patients relatives needed medical staffs to care for the patients; the rate of medical staffs interested in psychological care for patients was 62.7% but their main skills were of interpretation and encouragement. The leading boards of the surveyed hospitals strongly supported to need teams of experts to care psychologically for patients, in which bachelors of clinical psychology are the most suitable in this issue. Keywords Psychological difficulties; Psychology patients; Clinical Psychology References [1] WHO, Declaration of Alma-Ata, International Conference on Primary Health Care, Alma-Ata, USSR, 1978, 6-12 [2] WHO, Global status report on communicable diseases 2010. [3] WHO, Highlights global underinvestment in mental health care, 2011. [4] WHO, Integrating mental health into primary care: a global perspective", 2008. [5] Bộ Y tế, Hướng dẫn công tác điều dưỡng chăm sóc người bệnh trong BV, 2011. [6] Bộ Y tế, Đề án Phát triển nghề Công tác xã hội trong ngành Y tế giai đoạn 2011-2020, 2011. [7] Nguyễn Văn Ngân, Nguyễn Văn Nhận, Nguyễn Sinh Phúc, Tâm thần học đại cương và tâm lý y học, Học viện Quân y, (1998), 173-199. [8] Abigail Zuger, Work Habits of the 21st-Century Intern, J Gen Intern Med, (2013). [9] Johanna I Westbrook, Christine Duffield, How much time do nurses have for patients? a longitudinal study quantifying hospital nurses' patterns of task time distribution and interactions with health professionals, BMC Health Serv Res,11, (2011), 319. [10] Bộ Giáo dục và Đào tạo (2012), Thông tư số 01/2012/TT - BGDĐT ngày 13 tháng 01 năm 2012 của Bộ trưởng Bộ GD&ĐT về Khung chương trình Giáo dục đại học.